STUDY OF THE INFLUENCE OF TEETH CORRECTION OF METAL-POLYMER HELICAL SPUR GEARS ON BEARING CAPACITY AND DURABILITY: PART. 2. GEARS DURABILITY - Чернець, Мирон; Корнієнко, Анатолій; Чернець, Юрій (Problems of Friction and Wear, 2022)
According to the author’s method of calculating metal and metal-polymer gears, a study of the effect of height correction of the engagement of helical spur gears on durability was carried out. The durability of metal-polymer gears with a gear made of two types of polyamides was evaluated at different tooth helix angles and tooth shift coefficients. Quantitative and qualitative regularities of the influence of both factors on the minimum durability have been established, taking into account the parity teeth engagement. It was established that in a transmission with a gear made of polyamide composite PA6+30CF, the durability will be up to 2.4 times higher than that of unfilled polyamide PA6 and will not depend on the value of the tooth shift coefficients. The gears durability is significantly affected by both the corrrection of the engagement and the teeth helix angle. Quantitative and qualitative regularities of this influence were obtained. The existence of an optimum of tooth shift coefficients, at which the durability of the transmission will be the highest, has been established.